A Qualitative Study of the Validity and Reliability of a Psychological Well-being Training Package Based on Well-Being and Ill-Being Among Retired Nurses in Isfahan - Dorri , Akbar; Ghojavand, Kazem; Gorji , Yousef (Mental Health and Lifestyle Journal, 2024)
Retirement among nurses, due to chronic occupational stress, is frequently associated with experiences of ill-being and diminished psychological well-being. Previous research in Iran has paid limited attention to the lived experiences of retired nurses. The present qualitative study was conducted to deeply explore the experiences of ill-being and psychological well-being among retired nurses and to develop a counseling package based on these findings. This qualitative study employed Braun and Clarke’s (2006) thematic analysis approach. Data were collected through in-depth, semi-structured interviews with 19 retired nurses, selected via purposive sampling until theoretical data saturation was achieved. Data analysis followed six stages: familiarization with the data, generating initial codes, searching for themes, reviewing themes, defining and naming themes, and producing the final report. Analysis of the data yielded 440 meaning units and 15 main themes. Components related to psychological well-being included “self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth.” Components of ill-being comprised “displeasure with leisure activities, dissatisfaction with physical health status, displeasure with living environment, daily stressors, reduced interpersonal relationships, dissatisfaction with financial status, and feelings of hopelessness and despair.”  The findings indicate that the designed educational-counseling package possesses adequate content and face validity and can effectively enhance the psychological well-being of retired nurses. The results underscore the necessity of developing targeted educational interventions to provide psychological and social support for this population.